Le paysan de Paris de Louis Aragon: Écriture du labyrinthe et labyrinthe de l'écriture - Mesana , Corinne (Amaltea. Revista de Mitocrítica, 2009)
In 1920s, Louis Aragon, following his soul mates in the surrealist adventure, searched for the hidden reality during his wanderings in the depths of the city. Le paysan de Paris is a living document of this quest and one can find in that novel a revitalised image of the labyrinth, an archetype brought to life in both the story that is told and the way in which it is narrated. The description of urban places like the Passage of the Opera or the Buttes-Chaumont reveals a euphemised labyrinth, a place of encounters and forbidden passions and full of the most unexpected correspondences between diverse elements of the real. It becomes the space of the initiatic quest where the woman is the initiator and the traditional Minotaur is absent. This challenges the narrator/author to pursue the initiation to erotic life and to recreate the magic of the surreal. As the story is recounted, the surrealist account becomes labyrinthine. Its writer appears to be Daedalus building a complex narrative and risking to lose his reader along the way with numerous secondary accounts and various visual documents interrupting the main account. A new mode of writing, the labyrinthine writing, is on the move.